2009
DOI: 10.1093/hmg/ddp007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of imputation-based association in and around the integrin- -M (ITGAM) gene and replication of robust association between a non-synonymous functional variant within ITGAM and systemic lupus erythematosus (SLE)

Abstract: We recently identified a novel non-synonymous variant, rs1143679, at exon 3 of the ITGAM gene associated with systemic lupus erythematosus (SLE) susceptibility in European-Americans (EAs) and African-Americans. Using genome-wide association approach, three other studies also independently reported an association between SLE susceptibility and ITGAM or ITGAM-ITGAX region. The primary objectives of this study are to assess whether single or multiple causal variants from the same gene or any nearby gene(s) are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 31 publications
6
103
0
2
Order By: Relevance
“…The locus that encodes ITGAM on chromosome 16 provided a strong association with susceptibility to SLE in separate genome-wide association studies (25,26) and replication studies of multiple populations (27) reaching an odds ratio of 1.78 (1.56 -2.03). The missense SNP, rs1143679, results in an amino acid change from arginine to histidine at position 77 (R77H) in the extracellular I/A ligand-binding domain of CD11b.…”
Section: Discussionmentioning
confidence: 99%
“…The locus that encodes ITGAM on chromosome 16 provided a strong association with susceptibility to SLE in separate genome-wide association studies (25,26) and replication studies of multiple populations (27) reaching an odds ratio of 1.78 (1.56 -2.03). The missense SNP, rs1143679, results in an amino acid change from arginine to histidine at position 77 (R77H) in the extracellular I/A ligand-binding domain of CD11b.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5,[14][15][16][17][18][19] Two studies were excluded as the number of allele could not be extracted. 18,19 Thus, seven studies met the inclusion criteria.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…4 Although studies have suggested that ITGAM allele may confer susceptibility to SLE, investigations performed in different ethnic groups yielded apparently inconclusive results regarding the disease susceptibility conferred by specific polymorphism. Han et al 5 demonstrated that rs1143679, which converts Arginine 77 to Histidine explains the association of rs9937837 or rs11574637 with SLE and best explains the ITGAM-SLE association. The study by Yang et al 3 found that logistic regression analysis on Thai samples indicates that rs1143679 remains significant when controlling the effect of rs9888739 or rs1143678.…”
Section: Introductionmentioning
confidence: 99%
“…193 A study of ITGAM in 661 Korean and 176 Japanese patients with SLE found that rs1143679 was monomorphic, in contrast to the results of previous Caucasian studies. 194 PXK. PXK encodes the phox homology domain containing serine/threonine kinase that binds to and modulates Na-and K-ATPase activity, and has five splice isoforms that are widely expressed in human tissues.…”
Section: 187mentioning
confidence: 99%